Positive outcomes with neoadjuvant chemotherapy in the management of colovesical fistula in cancer: a case report and literature review - Tang, Song; Li, Xinjun; Guo, Donghua; Zhuo, Fan (Frontiers in Pharmacology, 2024)
Colovesical fistula (CVF) is usually developed from colonic diverticulitis, followed by tumor. Traditional surgery is usually completed in one or more stages. For complex cancerous CVF, radical resection is more difficult. We report a 62-year-old male patient diagnosed with sigmoid colon cancer combined with sigmoid vesical fistula. In the course of treatment, in addition to conventional surgery, neoadjuvant chemotherapy (NAC) was innovatively used. The sigmoid tumor and fistula were significantly shrunken. Radical surgery achieved negative margins.